PEMANFAATAN LIMBAH PULP KAKAO MENJADI NATA DE CACAO - Nurfaillah Nurfaillah; Masri Masri; Eka Ratna Sari; Patang Patang (Jurnal Pendidikan Teknologi Pertanian, 2018)
This community service aims to empower the unproductive community in Wonosari Village through the utilization of cocoa pulp waste into Nata De Cacao. This method of community service is divided into three stages: preparation stage, implementation stage, and final stage. The result of community service is the community has handled the utilization of cocoa bean pulp waste into Nata De Cacao. The society's understanding of the making of Nata De Cacao is quite high. But after we do the evaluation, people still need guidance in making Nata De Cacao. People love the Nata De Cacao that we make when conducting training on the utilization of cacao bean pulp waste. After we deliver the training, the community is well received and their thinking starts to open with the utilization of cacao pulp waste into Nata De Cacao can reduce environmental pollution and can be used as an opportunity for entrepreneurship. Therefore, with the utilization of this pulp waste can change the behavior of unproductive communities to be productive.